Vinasse and Its Influence on Ant (Hymenoptera: Formicidae) Communities in Sugarcane Crops - Saad, L. P.; Souza-Campana, D. R.; Bueno, O. C. [UNESP]; Morini, M. S. C. (Oxford Univ Press Inc, 2017)
Sugarcane is an important crop within the Brazilian socioeconomic landscape. There is a constant need for approaches to increase sustainability at all steps of the production chain. Irrigating sugarcane crops with vinasse is one of these approaches, because vinasse is a residue of sugarcane processing that can be used to fertilize these same crops. However, due to its chemical properties, vinasse may be harmful to soil fauna. Analyzing the structure and functional organization of ant communities is a fast and practical way to monitor sites affected by the addition of chemicals. This study compared the structure of soil ant communities in vinasse-irrigated sugarcane crops to those in secondary forests adjacent to the crops. In total, 32 genera and 107 species of ants were observed; of these, 30 species foraged in crop fields and 102 foraged in forests. Twenty-five percent of the species were present in both crops and forests. Ant communities in crop soil had poorer taxonomic composition and lower richness in each functional group compared to communities in forest remnants. However, regardless of vegetation type, epigeic ants were more diverse, and Dorymyrmex brunneus (crop) and Pachycondyla striata (forest) were very frequent. Vinasse did not increase the diversity of epigeic and hypogeic ants, but it may affect the community composition.
Keywords: agriculture; beneficial arthropod; biodiversity; community ecology